2017
DOI: 10.1111/imj.13190
|View full text |Cite
|
Sign up to set email alerts
|

Timely initiation of chemotherapy: a systematic literature review of six priority cancers – results and recommendations for clinical practice

Abstract: This review evaluated the association between time-to-chemotherapy (TTC) and survival in six priority cancers. A systematic review of the literature was undertaken for papers indexed in the MEDLINE and Cochrane Library databases from the earliest index until April 2014. The methodology used has been published in a separate paper (Guidelines for timely initiation of chemotherapy: a proposed framework for access to medical oncology and haematology cancer clinics and chemotherapy services). The optimal timing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 69 publications
0
35
0
1
Order By: Relevance
“…4 Most studies show no relationship between time-tochemotherapy and their survival rate. 26 However, it should be noted that in these review articles, the number of cases collected is generally very low, with the highest number of patients only 10 583. 26 Another study showed time intervals from diagnosis to treatment were not associated with survival outcomes in NSCLC.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…4 Most studies show no relationship between time-tochemotherapy and their survival rate. 26 However, it should be noted that in these review articles, the number of cases collected is generally very low, with the highest number of patients only 10 583. 26 Another study showed time intervals from diagnosis to treatment were not associated with survival outcomes in NSCLC.…”
Section: Discussionmentioning
confidence: 87%
“…26 However, it should be noted that in these review articles, the number of cases collected is generally very low, with the highest number of patients only 10 583. 26 Another study showed time intervals from diagnosis to treatment were not associated with survival outcomes in NSCLC. 27 In this previous study, they discussed NSCLC patients with different treatment such as surgery, radiotherapy, systemic therapy and palliative care, which were not discussed in our study.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, Sun Z. et al, [16] emphasized the importance of the timely initiation, which suggested delays beyond 6 weeks were associated with a compromised survival. In addition, Alexander M. et al, [6] systematic analyzed 7 articles about the initiation intervals, concluded that PAC should commence within 4 -8 weeks for curative colorectal neoplasm patients. More recent study by Nachiappan S. et al, [17] put forward that people would be benefit from initiation of PAC within 8 weeks regardless of reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…Updated international guidelines recommend that maximum interval from the development of a management plan to chemotherapy initiation is 12 weeks for PAC. Most clinical trials mandate the initiation of adjuvant chemotherapy for surgically resected colorectal cancer within 4 -8 weeks post-surgery [6]. A large, randomized study conducted with Stage II/III CRC patients in the Hospital Episode Statistics (HES) reported that PAC initiation beyond 8 weeks significantly reduced overall survival (OS) in patients, compared to those who received it within 8 weeks, and every 2 weeks increments in the delay accompanied by progressively worse OS [7].…”
Section: Introductionmentioning
confidence: 99%
“…The study by Wright et al [8] reported that a TTC of 6 weeks or less did not influence OS (overall survival rates). However, the review article by Alexander et al [9], recommends starting chemotherapy within 4 weeks of surgery.…”
Section: Introductionmentioning
confidence: 99%